Temperature, cloud structure, and dynamics of venus middle atmosphere by infrared remote sensing from pioneer orbiter. - Taylor, F; Diner, D; Elson, L; McCleese, D; Martonchik, J; Delderfield, J; Bradley, S; Schofield, J; Gille, J; Coffey, M (1979)
Further results from the Venus orbiter radiometric temperature experiment (VORTEX) on the Pioneer orbiter are presented. These are used to characterize the three-dimensional temperature field, the cloud structure, and the dynamics of the 60-to 130-kilometer altitude region of the Venus atmosphere. One of the new discoveries is a "dipole" structure at high latitudes, with two hot spots rotating around the pole, surrounded by banks of cold cloud.